EDUKASI DAN PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE PADA PENDIDIKAN SEKOLAH MENENGAH ATAS DALAM MENGHADAPI ERA DIGITALISASI - Juliani, Dian; Purwita, Citra; Ulya Fitra, Reishi Radhiyatul (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Artificial Intelligence (AI) is a concept related to technological advances in the Industry 4.0 and Society 5.0 era. AI is a computer program that involves integrated machine learning, hardware, and software. This concept is inspired by the neocognitron pattern in the human brain and uses hardware and software science to achieve its function. In the development of Industry 4.0, AI has been widely used in various fields, including education. The aim of this community service activity is to provide education and training to students and educators in the use of Artificial Intelligence to simplify the tasks of educators and provide new learning experiences for students. This activity was attended by 90 students and 20 teachers. Artificial Intelligence education and training activities were carried out at Godean 1 State High School, Sleman Regency, Yogyakarta Special Region. The results of community service activities in the form of Artificial Intelligence education and training for students and teachers are that teachers understand the importance and use of AI in an interesting and enjoyable learning process and students understand the use of AI to assist in the learning process.